Molecular dynamics studies of an endoglucanase from fusarium oxysporum - Noorbatcha, Ibrahim Ali; Waesoho, Shukree; Mohd. Salleh, Hamzah (2010)
Abstract: Use of computational methods to model and design new enzymes with enhanced functionalities is an emerging technology. In this work endoglucanase obtained from Fusarium oxysporum is modeled using homology modeling, and the dynamics of this enzyme in vacuum and water medium is examined to analyze the effect of the environment on the structural and dynamical factors during the simulation. It is shown that the presence of water as the solvent medium has significant effects on the dynamics of the enzyme. The structural compactness of the enzyme increases, and the fluctuations of the backbone and the enzyme as a whole entity, becomes smooth in water. These effects are attributed to the presence of electrostatic network of interactions including hydrogen bonds in the water as the solvent medium. This study shows the importance of including appropriate solvent models in molecular dynamics simulations.